2023
DOI: 10.3390/nu15071614
|View full text |Cite
|
Sign up to set email alerts
|

Bee Products and Colorectal Cancer—Active Components and Mechanism of Action

Abstract: Colorectal cancer is one of the most common malignancies in the world. Lifestyle and eating patterns may have a significant impact on the prevention of this type of cancer. Bioactive food ingredients influence the gut microbiome and can have a protective effect. Bee products (honey, propolis, royal jelly, and bee venom) or pharmacologically active fractions obtained from them are widely used in many fields of medicine, pharmacy, and cosmetics. Some evidence suggests that bee products may have anti-cancer poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Thus, RJ reduced genotoxicity and DNA damage when used with cyclophosphamide. Following treatment with 5-FU, RJ reduced the cell viability and IC50 of 5-FU in colorectal cancer cells [ 273 , 274 ]. It is also capable of initiating apoptotic events in breast or liver and kidney cancer cells in animals treated with thymoquinone or cisplatin, respectively [ 269 , 275 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
“…Thus, RJ reduced genotoxicity and DNA damage when used with cyclophosphamide. Following treatment with 5-FU, RJ reduced the cell viability and IC50 of 5-FU in colorectal cancer cells [ 273 , 274 ]. It is also capable of initiating apoptotic events in breast or liver and kidney cancer cells in animals treated with thymoquinone or cisplatin, respectively [ 269 , 275 ].…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
“…Research has shown that isoflavones and flavonoids of BP restrain the cell cycle at G1 and or G2/M stages and upregulate the expression of pro-apoptotic genes and dysfunction of the capability of enzymes associated with the growth and development of tumor cells while hindering the activity of intermediates such as fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) and also inhibiting the production of ROS ( 177 , 178 ). Wang et al concluded that BP polysaccharides (extracted from Rosa rugosa ) exhibited anticancer activity in vitro against HCT116 (human colon carcinoma) and HT-29 (colon cancer) cells in a dose-dependent way ( 179 , 180 ). Furthermore, BP samples of three stingless bees, i.e., Heterotrigona itama, Tetrigona apicalis, and Geniotrigona thoracica (from Malaysia) were tested in vitro upon MCF-7 (breast adenocarcinoma human cell lines) and MCF-10A (mammary epithelial human cell lines), which inhibits the proliferation of both tumor cell lines in a dose-dependent way ( 181 ).…”
Section: Apitherapymentioning
confidence: 99%